THE IMPLEMENTATION OF DIGITAL FLIPBOOK TO ENHANCE STUDENTS’ READING COMPREHENSION - Nurhapsari, Happy Annisa; Handayani, Sri (ENGLISH RESEARCH JOURNAL, 2025)
The research aims to investigate the implementation of Digital Flipbook (DigiFlip) as an English teaching and learning media to improve students’ reading comprehension in tenth grades of MAN 1 Surakarta during the 2024/2025 academic year. The study used a Classroom Action Research (CAR) design and collected qualitative data through observation, documentation, and questionnaires. Quantitative data was collected through pre-test, post-test 1, and post-test 2, and analyzed using the Miles and Huberman triangulation method. The results showed that the application of digital flipbook effectively improved students’ reading comprehension, with an average score increase of 62 in the pre-test, 71 in post-test 1, and 86 in post-test 2. The classroom environment also showed a significant improvement, with students becoming more pleasant, enthusiastic, active, and conducive during the teaching-learning process. The study’s findings highlight the potential of digital flipbooks in enhancing students’ reading comprehension and English language learning. Keywords: Reading comprehension; digital flipbook; classroom action research